Mesophotic Depth Biogenic Accumulations (“Biogenic Mounds”) Offshore the Maltese Islands, Central Mediterranean Sea - Bialik, Or M.; Varzi, Andrea Giulia; Durán, Ruth; Le Bas, Timothy; Gauci, Adam; Savini, Alessandra; Micallef, Aaron (Frontiers in Marine Science, 2022)
The mesophotic domain is a poorly explored part of the oceans, notably in the Mediterranean Sea. Benthic communities in these depths are not well documented and as such are under higher risk from anthropogenic impacts. Hard substrate habitats in this depth window are not common and are a key ecotope. The Malta Plateau in the central Mediterranean, which is characterised by low sedimentation rates, offers a potentially unexplored domain for these features. Bathymetric and backscatter data offshore of the eastern coast of the island of Malta were used to identify >1700 small structures in mesophotic depths. These structures were verified to be biogenic mounds by dives. The mounds extend from several meters to tens of meters in diameter and occur in two main depth windows - 40 to 83 meters below present sea level (mbpsl) and 83 to 120 mbpsl - each formed probably in a different stage during the last glacial cycle. The mounds are composed of interlocking bioconstruction by encrusting organisms and are colonised by sponges and various cold water corals (most of which are protected; e.g. Madrepora oculata). This unique and important habitat is currently under grave threat by human activity, most immediately by trawling and anchoring activity.